How do adolescents experience sexting in dating relationships? Motivations to sext and responses to sexting requests from dating partners. (February 2020) - Reed, Lauren A.; Boyer, Margaret P.; Meskunas, Haley; Tolman, Richard M.; Ward, L. Monique
Highlights: Surveyed 947 high school students about sexting behaviors and dating. Girls more likely than boys to receive pressure to sext. Girls more likely to have negative emotional responses to sexting requests. Individual factors associated with positive or negative emotional responses to requests. Most sexting is wanted, but gender and individual factors matter in experience. Abstract: Although most sexting among adolescents occurs in the context of a dating relationship, less is known about adolescents' motivations to sext and the emotional experience of sexting within dating relationships. The current study surveyed 947 high school students about their sexting behaviors, motivations to sext, and emotional reactions to sexting requests from dating partners. Although both girls and boys reported sexting behaviors, girls were more likely to report receiving pressure to sext and negative emotional responses to sexting requests from a dating partner. Among girls, greater self-sexualization, lower religiosity, perceiving peer sexting as more common, and being older predicted more positive emotional reactions to sexting requests from a partner. Greater attachment anxiety, lower self-sexualization, greater religiosity, and being younger predicted more negative emotional reactions for girls. Among boys, lower attachment avoidance, greater self-sexualization, and lower religiosity predicted more positive emotional reactions to sexting requests. Only lower levels of self-sexualization predicted negative emotional reactions to sexting requests for boys. These findings support that sexting is a gendered experience for adolescents in dating relationships and that although most sexting between partners is wanted, certain adolescents may be more at risk for experiencing negative consequences from sexting.